Maternal and neonatal outcome of spontaneous versus induced labour at term - Shrestha, Dipty; Bajracharya, Junu; Shrestha, Nira Singh (Journal of Kathmandu Medical College, 2016)
Background: Induction of labour today has become the most common obstetric intervention. It is increasing worldwide but there are still controversies regarding its benefits.Objective: To compare the maternal and neonatal outcomes of elective induction of labour with spontaneous onset of labour in pregnant women from 40 to 42 weeks of gestation at Kathmandu Medical College and Teaching Hospital (KMCTH).Methods: This was a comparative hospital based study that was conducted at KMCTH from 15th April 2013 to 15th April 2014. Three hundred women with singleton pregnancies from 40 to 42 weeks of gestation without any risk factors were enrolled and among these 150 women were selected for induction of labour by purposive sampling. Among these, those with Bishops score less than six were induced with prostaglandin E2 which was administered intracervically followed by intravenous infusion of oxytocin in an escalating dose. Those with Bishops score more than six were directly induced with intravenous oxytocin in an escalating dose. Another 150 women were allowed to go into spontaneous onset of labour. The outcome that were looked upon were mode of delivery, rate of caesarean section, maternal morbidities which included post partum haemorrhage (PPH), haematoma, third and fourth degree perineal tears, neonatal intensive care unit (NICU) admission and also neonatal morbidities and mortality.Results: Among 150 pregnant women undergoing induction of labour, 82 (54.6%) had normal delivery, 10 (6.6%) had instrumental delivery and 58 (38.8%) had caesarean section whereas among another 150 pregnant women with spontaneous onset of labour 57 (38%) had normal delivery, 9 (6%) had instrumental delivery and 84 (56%) had caesarean section. Regarding the neonatal morbidities, NICU admissions were more in those with spontaneous onset of labour than induced labour; 20 (13.3%) and 14 (9.3%) respectively. The commonest indication for neonatal intensive care unit admission was meconium stained liquor.Conclusion: Elective induction of labour is associated with lesser rates of caesarean section and does reduce the NICU admissions when compared with spontaneous onset of labour.Journal of Kathmandu Medical College, Vol. 4(1) 2015, 8-11